Levothyroxine Therapy Adequacy, Dose Estimation and Vitamin D Effect Assessment in a Sample of Iraqi Female Patients with Different Causes of Hypothyroidism - Al-Shimmran, Ban A.; M. Anwer, Zinah; H. Al-Jarrah, Bassam (Iraqi Journal of Pharmaceutical Sciences, 2020)
Exogenous levothyroxine dose modulation and euthyroidism achievement is a persistent challenge in clinical settings. This study strives to assess the adequacy of treatment and identify the patients’ factors that can be used to estimate the euthyroid levothyroxine dose. A secondary objective was to assess vitamin D supplementation impact on thyroid status. A review of a prospectively collected information from 142 female patients from Baghdad Center of Nuclear Medicine from June 2019 until March 2020 who were receiving levothyroxine for different causes was done. After a follow-up period, the patients’ thyroid tests were assessed and the euthyroid doses for each cause category were statistically analyzed. Thyroid function was assessed before and after three months of vitamin D supplementation for 29 out of 50 patients who measured its level. Sixty-six patients (47%) of the sample were inadequately replaced